Fuzzy logic inference algorithms utilization in the economic potential growth management system of the real estate development company - Rosynskyi, A. (Ways to Improve Construction Efficiency, 2023)
The article defines the need to introduce fuzzy logic inference algorithms into the economic potential growth management system of the real estate development company. The use of fuzzy inference algorithms in the study of influencing factors on the profitability of development projects as prerequisites for economic potential growth of the real estate development company is proposed. It was determined that the increase in profitability and economic potential growth of the development company are particularly affected by managerial decisions regarding the development projects’ pricing policy, the justification of which requires the processing of complex economic information using fuzzy logic algorithms. As a result of a selective study of the price policy of various similar development projects of multi-story residential buildings in Kyiv, the factors affecting the change in prices for primary residential real estate were identified and grouped. A fuzzy logic inference algorithm was developed for the system of identified impact factors, which consists of separate subsystems of fuzzy inference for each factor group (apartment, building and time impact subsystems), which allows obtaining additional information necessary for making informed management decisions regarding the economic potential growth of a real estate development company. The characteristics of the input and output variables terms membership functions for all impact subsystems were determined, as well as sets of rules (knowledge bases) of each subsystem were developed. The process of creating and implementing the developed algorithm in the Fuzzy Logic Designer environment of the MATLAB software complex is presented, as well as the possibilities of using the functionality of its environment in order to obtain dynamic numerical and graphic data (in particular, graphs and surfaces) for the analysis and research of the state, characteristics and trends of development company economic processes in real time. The expediency of fuzzy logic inference algorithms utilization in the economic potential growth management system of the real estate development company has been proven.